Cultural adaptation and validation of the Norwegian version of the swallowing quality of life questionnaire (SWAL-QOL) - Maribeth Caya Rivelsrud; Melanie Kirmess; Lena Hartelius (Health and Quality of Life Outcomes, 2019)
Abstract Introduction Oropharyngeal dysphagia (OD) is a disorder that can have devastating and long lasting effects on a person’s medical, mental and psychosocial well-being, thus negatively impacting quality of life. There is currently no validated dysphagia-specific quality of life instrument in Norway. This project aims to evaluate the psychometric properties of the culturally adapted Norwegian version of SWAL-QOL (Nor-SWAL-QOL). Methods The original SWAL-QOL was translated into Norwegian according the international translation guidelines. A group of 102 persons with OD and a group of 123 healthy controls were recruited to assess the validity and reliability of the Nor-SWAL-QOL. Correlation analysis of the Nor-SWAL-QOL and the Short Form 36 (SF-36) and correlation analysis of OD group and control group Nor-SWAL-QOL subscale scores were computed to determine convergent, discriminant, and known-groups validity which help comprise construct validity. Internal consistency, test-retest reliability and intraclass correlation coefficient (ICC) were computed for reliability. Results Convergent and discriminant validity was demonstrated between Nor-SWAL-QOL subscales and SF-36 domains, and distinguished between persons with and those without oropharyngeal dysphagia on all subscales and on the symptom frequency battery (p < 0.001). Additionally, the Nor-SWAL-QOL differentiated between symptom severity levels within the OD group; those requiring food and liquid modifications and those who are tube fed and not tube fed. Nor-SWAL-QOL showed good reliability with adequate internal consistency (Cronbach’s α ≥0.70), test-retest reliability (Spearman’s rho values 0.68–0.90) and ICC values (0.67–0.89) for all subscales and for the symptom frequency battery. Conclusion Access to valid and reliable dysphagia-specific QoL outcome measures for health care practitioners, dysphagia clinicians and researchers is necessary for comprehensive assessment and treatment outcome measures. The Nor-SWAL-QOL exhibits sufficient psychometric properties for implementation in the Norwegian population.